EFFECTIVE STRATEGIES FOR BEBEK CAROK SIDOARJO RESTAURANT: ANALYZING BRAND IMAGE, PRODUCT QUALITY AND PRICE PERCEPTIONS INFLUENCING CONSUMER PURCHASING DECISIONS - Syahrul Afandi; Muhammad Yani; Misti Hariasih (International Journal of Economic Integration and Regional Competitiveness, 2024)
General Background: Traditional Indonesian culinary culture faces challenges as modern food products increasingly dominate consumer preferences. To preserve and promote traditional cuisine, some entrepreneurs and influencers have introduced strategies to enhance brand image, maintain product quality, and offer competitive prices. Specific Background: One such example is Bebek Carok Restaurant, owned by influencer Tretan Muslim in Sidoarjo, which aims to attract more consumers by highlighting traditional Indonesian dishes. Knowledge Gap: However, limited research exists on the impact of brand image, product quality, and price perception on consumer purchasing decisions in traditional food restaurants. Aims: This study aims to analyze the influence of brand image, product quality, and price perception on purchasing decisions at Bebek Carok Restaurant in Sidoarjo. Results: Using a quantitative approach and a sample of 96 respondents, the findings reveal that brand image, product quality, and price perception each have a positive and significant effect on purchasing decisions at the restaurant. Novelty: This research provides insights into the role of brand image and quality perceptions in driving consumer behavior in traditional culinary markets, a relatively underexplored area in Indonesia. Implications: The results offer valuable guidance for traditional food entrepreneurs, demonstrating the importance of maintaining strong brand image and product quality, alongside competitive pricing, to enhance consumer engagement and boost sales.